Investigation of the physico-chemical properties of Ni-Mg-Al-La catalysts from ultrasound-assisted synthesis - H. Kalawoun; C. Ciotonea; M. Marinova; C. Gennequin; F. Delattre (Ultrasonics Sonochemistry, 2024)
This work reports on the ultrasonic synthesis of layered double hydroxides (LDH), also known as hydrotalcite-type materials. We have studied the influence of ultrasonic irradiation parameters (power, time, temperature) on the physicochemical properties of Ni2Mg4Al1.8La0.2 hydrotalcite-type precursors and related mixed oxides (MO). The low-frequency acoustic cavitation (22 kHz) was applied during the precipitation and aging steps of co-precipitation synthesis and the results were compared to the classical preparation route. The materials were characterized by ATR-FTIR, XRD, N2 adsorption–desorption, SEM-EDX, S/TEM-HAADF, and XPS. Using the combination of acoustic cavitation-assisted precipitation and aging steps, XRD experiments show a higher purity hydrotalcite phase and a better incorporation of lanthanum ions into the LDH structure. As expected, morphological characterization shows a reduction in average crystallite size and an increase in surface area and pore volume, combined with a drastic reduction in synthesis time (45 min at room temperature versus 19 h at 60 °C in conventional synthesis). The insertion of a larger quantity of La is observed by S/TEM-EDSX mapping which also shows a better distribution of lanthanum atoms within the LDH and mixed oxide structures.